Rapid antigen tests for SARS-CoV-2: a synopsis of the medical evidence - Wertenauer, Christoph; Pfeifer, Caroline; Roskos, Martin; März, Winfried (Diagnostic microbiology and infectious disease, 2023)
SARS-CoV-2, the causative agent of the COVID-19 pandemic, continues to influence health, economy, and stability worldwide. Diagnostic testing for SARS-CoV-2 is important to contain the COVID-19 pandemic. With the commercial availability of certified antigen (Ag) rapid diagnostic tests (RDTs), which can be used to identify an infection with SARS-CoV-2 an easy-to-use tool was introduced. Self-tests can offer advantages to complement professionally administered rapid antigen detection or nucleic acid amplification testing (NAAT). Compared to real-time polymerase chain reaction (RT-PCR), Ag-RDTs are cost inexpensive, do not need specialized laboratory equipment, facilitating high-throughput testing. However, Ag-RDT sensitivities are strongly dependent on the viral load within the specimen, which has limited their application in clinical settings so far. The methodical limitations of Ag-RDTs may produce false negative test results, particularly when specimens with low viral loads are examined. This may facilitate viral transmissions if protective measurements are lifted mistakenly.